2015
DOI: 10.1001/jamaophthalmol.2015.0980
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofCYP1B1Mutations in Juvenile Open-Angle Glaucoma With Advanced Visual Field Loss

Abstract: IMPORTANCEJuvenile open-angle glaucoma (JOAG) is a severe neurodegenerative eye disorder in which most of the genetic contribution remains unexplained.OBJECTIVE To assess the prevalence of pathogenic CYP1B1 sequence variants in an Australian cohort of patients with JOAG and severe visual field loss. DESIGN, SETTING, AND PARTICIPANTSFor this cohort study, we recruited 160 patients with JOAG classified as advanced (n = 118) and nonadvanced (n = 42) through the Australian and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…27,32 Four cases carried two qualifying variants in these genes. One participant was compound heterozygous and two were homozygous for CYP1B1 qualifying variants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…27,32 Four cases carried two qualifying variants in these genes. One participant was compound heterozygous and two were homozygous for CYP1B1 qualifying variants.…”
Section: Resultsmentioning
confidence: 99%
“…56 This difference may be in part due to the younger age at diagnosis in the French JOAG study (median ¼ 40, range, 13-52), as our previous study examining the prevalence of CYP1B1 variants in JOAG found a 6.8% rate. 27 Additionally, the three cases in the French study harbored a known polymorphic variant, p.(Ala443Val), which brings their true prevalence to 3.4%. The case cohort in the New Zealand study included pseudoexfoliative glaucoma and ocular hypertension as well as POAG suspects, which makes any direct comparison The data from 218 cases and 1096 controls are presented.…”
Section: Contribution Of Known Poag Genes Inmentioning
confidence: 91%
See 3 more Smart Citations